Analysis of Coffee Farming Income in Barambang Village, Sinjai Borong District, Sinjai Regency - Haerul Amri; Fadilah Nurdin; Megawati; Putra Astaman (Sustainable Agribusiness Review, 2025)
This study aims to determine the factors that influence coffee farming businesses as well as the amount of income and the feasibility of coffee farming businesses in Barambang Village, Sinjai Borong District, Sinjai Regency. The research method used a quantitative descriptive approach with the determination of coffee farmer respondents selected using purposive sampling. The data were analyzed to determine the factors that influence coffee farming income, such as land area, production costs, selling prices, and income variables, and were also calculated using feasibility analysis using the R/C ratio. The results showed that several factors, such as land area and selling prices, had a significant effect on coffee farmers' income. Income analysis showed the average income from coffee farming per planting season, which included total production costs. Based on the feasibility analysis, the R/C ratio value indicated that coffee farming in Barambang Village was feasible because the R/C ratio value was > 1.